2014
DOI: 10.1603/me13071
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Spatial Oviposition Activity ofAedes albopictus(Diptera: Culicidae) in Adriatic Croatia

Abstract: Seasonal and spatial ovipositional activity of Aedes albopictus (Skuse, 1894) was investigated in Split, South Croatia. During 2009 and 2010, 35 oviposition traps were used in this research. For studying oviposition behavior, mean egg density and Lloyd's mean crowding were used to define the dispersion of eggs into ovitraps and, together with Taylor's power law, to show aggregation degree. To show monthly distribution of egg density, Kriging interpolation was used. Oviposition activity started in April (week 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Mathematical modelling of the likelihood of dengue importation to Europe (taking into account dengue seasonality in the countries from which dengue could be imported, the number of reported dengue cases imported into Europe and the volume of airline travellers arriving from dengue-affected areas internationally) concluded that the risk of dengue importation is greatest in August, September and October [29]. Entomological monitoring in the Mediterranean region indicated that the development period for A. albopictus starts in April and closes in October/November with activity peaks from June/July to September [30,31]. The peak activity of A. albopictus populations in the south of Europe thus coincides with the seasonal peak of imported dengue cases in Europe which increases the risk of autochthonous transmission [29,32].…”
Section: Discussionmentioning
confidence: 99%
“…Mathematical modelling of the likelihood of dengue importation to Europe (taking into account dengue seasonality in the countries from which dengue could be imported, the number of reported dengue cases imported into Europe and the volume of airline travellers arriving from dengue-affected areas internationally) concluded that the risk of dengue importation is greatest in August, September and October [29]. Entomological monitoring in the Mediterranean region indicated that the development period for A. albopictus starts in April and closes in October/November with activity peaks from June/July to September [30,31]. The peak activity of A. albopictus populations in the south of Europe thus coincides with the seasonal peak of imported dengue cases in Europe which increases the risk of autochthonous transmission [29,32].…”
Section: Discussionmentioning
confidence: 99%
“…albopictus was investigated in Split, south Croatia where oviposition activity started in April and was completed at the beginning of December while mean egg density was highest from June to early September. (Žitko and Merdić 2014). By 2012, this species spread to coastal Croatia, including its islands.…”
mentioning
confidence: 98%
“…albopictus has been the most common species in the Croatia coastal area and now is widespread from Istria in the north through Dalmatia and islands to Dubrovnik in the south [17,18]. The first record of Ae.…”
Section: Aedes Albopictusmentioning
confidence: 99%
“…albopictus, one of the most important vectors of DENV and CHIKV is well-established in Croatia's coastal territory [17,18] and the Zagreb area.…”
Section: Introductionmentioning
confidence: 99%